Download presentation

Presentation is loading. Please wait.

Published byKeven Levell Modified over 9 years ago

1
2-8 Inverse of a sum and simplifying

2
Inverse of a Sum What happens when we multiply a rational number by -1? The product is the additive inverse of the number. The Property of -1 For any rational number a, (negative one times a is the additive inverse of a) the property of -1 enables us to find an equivalent expression for the additive inverse of a sum

3
Examples -(3 + x) = -1(3 + x) Using the distributive property = -3 – x -(3x + 2y + 4) = -1 (3x + 2y + 4) Using the distributive property = -3x – 2y – 4 Try this: a)-(x+2) b) - (5x +2y +8) c) -(a – 7) d) -(3c – 4d + 1)

4
Inverse of a Sum Inverse of a sum property For any rational numbers a and b, -(a + b) = -a + -b (The additive inverse of a sum is the sum of the additive inverses) The inverse of a sum property holds for differences as well as sums because any difference can be expressed as a sum. When we apply the inverse of a sum property we sometimes say that we “change the sign of every term” Example: rename each additive inverse without using parentheses -(5 – y) = -5 + y -(2a – 7b – 6) = -2a + 7b +6

5
Try this -(6 – t) -(-4a + 3t – 10) -(18 – m – 2n + 4t)

6
Simplifying Expressions Involving Parentheses When an expression inside parentheses is added to another expression as in 5x + (2x + 3), the associative property allows us to move the parentheses and simplify the expression to 7x + 3. When an expression inside parentheses is subtracted from another expression as in 3x – (4x + 2), We can subtract by adding the inverse. Example: Simplify 3x – (4x + 2) = 3x + ( - (4x + 2)) = 3x + (-4x – 2) = -x – 2

7
Example 5y – (3y + 4) = 5y -3y – 4 = 2y – 4 3y – 2 – ( 2y – 4) = 3y – 2 – 2y + 4 = (3y – 2y) + ( -2 + 4) = y + 2

8
Example x – 3(x + y) = x – 3x + (-3y) = x – 3x – 3y = -2x – 3y 3y – 2(4y – 5) = 3y – 8y + 10 = -5y + 10 h) 5x – (3x + 9) i) 5x – 2y – (2y – 3x – 4) j.) y – 9(x + y) k) 5a – 3(7a – 6)

9
Grouping Symbols Some expressions contain more than one grouping symbol. Parentheses (), Brackets [ ], and Braces { } are all grouping symbols we use in algebra. When an expression contains more than one grouping symbol, we start with the inner more parentheses and work our way out. [3 – (7+3) = [ 3 – 10] [8 – [9 – (12 + 5)]] = -7 = [ 8 – [ 9 – (17)] = [ 8 – [9 – 17] = [ 8 – [-8] = [8 - -8] = 16

10
Try this [ 9 – (6+ 4)] 3(4 + 2) – [ 7 – [ 4 – (6 + 5)]] [3(4 + 2) + 2x] – [4 (y + 2) – 3 (y – 2)]

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google